2016
DOI: 10.1177/1687814016666449
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of energy efficiency for electro-hydraulic composite braking system which is based on the regenerated energy

Abstract: A novel structure of the combined braking system based on the regenerative braking energy has been proposed to achieve simplified structure and energy-saving capability simultaneously, which includes the hydraulic regenerative braking system, electro-hydraulic braking system, and the power coordinate module. Theoretical contributions and managerial implications of the developed system are discussed. The corresponding mathematic models are developed, a fuzzy control method which can fulfill the power coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…In the current research on brake energy recovery at home and abroad, according to whether the brake pedal force is decoupled from the hydraulic braking force or not, the brake energy recovery system can be categorized into iterative regenerative braking system (RBS) and collaborative regenerative braking system (CRBS), and by comparing these two types of regenerative braking systems, a more e cient and concise brake energy recovery system is selected [11] .…”
Section: Selection Of Brake Energy Recovery Methodsmentioning
confidence: 99%
“…In the current research on brake energy recovery at home and abroad, according to whether the brake pedal force is decoupled from the hydraulic braking force or not, the brake energy recovery system can be categorized into iterative regenerative braking system (RBS) and collaborative regenerative braking system (CRBS), and by comparing these two types of regenerative braking systems, a more e cient and concise brake energy recovery system is selected [11] .…”
Section: Selection Of Brake Energy Recovery Methodsmentioning
confidence: 99%
“…Most of the regenerative brake systems of EV are composed of electrical systems, such as motor, power inverters, and battery, but Ma proposed a new combined brake system structure, including power coordinate module, electro-hydraulic brake system, and hydraulic regenerative braking system, and designed a simple fuzzy control method to coordinate the high-pressure and low-pressure accumulators. The simulation found that the liquid capacity and initial SOC of the energy storage accumulator are the key factors affecting the energy recovery efficiency, and the initial braking velocity is the determining factor of the total recovery energy [102]. A conventional regenerative brake system needs to store the recovered energy in a energy storage device, such as battery or super capacitor, and then the storage device supplies the electric energy to other electric equipment.…”
Section: Application In Electric Vehiclesmentioning
confidence: 99%
“…Laaleh Durali [8] designed a braking system for a cam-driven mechanism that maximizes the characteristics of the motor torque by combining electrical and hydraulic components, which can be fitted to each wheel and can be independently controlled for individual wheels, resulting in better stability of the vehicle during rapid acceleration or emergency braking. Ma [9] proposed a novel structure of a combined braking system based on regenerative braking energy, built a simulation model through Simulink to analyze the dynamic parameters such as the initial braking speed and the maximum braking pressure of the vehicle, and concluded that the initial braking speed of the vehicle is the key to affecting the total efficiency of braking energy recovery. The precise control of the hydraulic pressure of the wheel cylinder is a key technology of the linear control system.…”
Section: Introductionmentioning
confidence: 99%